Jawapan

  • Pengguna Brainly
2016-03-04T22:28:16+08:00
h(x) = 5(x)-4
g(x) = 2+mx
hg(x) = gh(x)

hg(x) = h{g(x)}
         = 5(2+mx) - 4
         = 10 + 5mx - 4
         = 6 + 5mx

6 + 5mx = gh(x)
g{h(x)} = 6 + 5mx
2 + m(5x-4) = 6 + 5mx
2 + 5mx - 4m = 6 + 5mx
4m = - 4
m = - 1
1 5 1
mcm mne bleh dpt 4m = -4
5mx - 5mx
2 - 6 = - 4
2016-03-04T23:26:56+08:00
5(2+mx)-4 = 2+m(5x-4)
10+5mx-4 = 2+5mx-4m
10-2-4+4m = 5mx - 5mx
4+4m = 0
4m = -4
m =  \frac{-4}{4}
m = -1
minta maaf , pada baris ke-3, tertinggal -4